Factors Influencing Virulence and Plaque Properties of Attenuated Venezuelan Equine Encephalomyelitis Virus Populations - Hearn, Henry J. (1969)
A minority of stable large-plaque virus increased proportionally in stored unstable attenuated (9t) Venezuelan equine encephalomyelitis virus populations. L-cell-grown progeny (9t2) of stored 9t showed large amounts of large-plaque virus and increased virulence. Small-plaque virus inhibited large-plaque virus but not the reverse. Serial passage of small-plaque virus from 9t2 yielded a strain (20t) that was more attenuated than 9t.